Characterization of NPM1 and FLT3-ITD Mutations in Iraqi Patients with AML (Medico Legal Update, 2021)
Acute myeloid leukemia is a malignant disease results from mutation in a multipotent haemopoietic stemcell. The study aimed to investigate NPM1 and FLT3-ITD mutations in Iraqi patients with AML and correlateresults with other clinical and laboratory findings. Fifty-eight AML patients, admitted to Baghdad TeachingHospital from October 2019 till March 2020 in addition to 25 normal controls, were included in the study.A detailed history, laboratory investigations including FLT3-ITD and NPM1 mutations were collected fromand analyzed. FLT3-ITD was detected in 17.24% of patients, NPM1 mutation in 10.34%. Most of thepatients are presented with pallor. FLT3-ITD mutation had a higher blast cell count (74%) while NPM1mutation had higher WBCs count.Conclusion: AML is common in middle age group, patients with NPM1 mutation had significantly higherWBCs count while patients with FLT3-ITD mutation have higher blast percentage compared with nonmutated patients.